2021
DOI: 10.1002/jso.26422
|View full text |Cite
|
Sign up to set email alerts
|

The role of neurotization in autologous breast reconstruction: Can reconstruction restore breast sensation?

Abstract: As the sophistication of microsurgical breast reconstruction continues to evolve, plastic surgeons are focusing on techniques to improve functional and psychosocial outcomes for patients, including breast sensation. Interest in neurotization of breast flaps, among both patients and surgeons, has grown significantly in recent years. This study aimed to review the outcomes of neurotization across autologous flap reconstructions, to provide a comprehensive analysis of the efficacy of this technique in improving p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 41 publications
1
18
0
Order By: Relevance
“…In breast reconstruction, several authors have described faster recovery and superior sensory reinnervation in neurotized free flaps. 7–9,11–16 Similarly, in extremity reconstruction, previous studies describe overall diminished sensory recovery gradually improving over time 2,10,17,18 and faster recovery in neurotized flaps. 10 In contrast, in oral cavity reconstruction using radial forearm flaps and latissimus dorsi flaps, sensory reinnervation has been shown in neurotized and nonneurotized flaps 19–21 with some authors reporting no superior improvement in flaps with nerval reconstruction.…”
mentioning
confidence: 80%
“…In breast reconstruction, several authors have described faster recovery and superior sensory reinnervation in neurotized free flaps. 7–9,11–16 Similarly, in extremity reconstruction, previous studies describe overall diminished sensory recovery gradually improving over time 2,10,17,18 and faster recovery in neurotized flaps. 10 In contrast, in oral cavity reconstruction using radial forearm flaps and latissimus dorsi flaps, sensory reinnervation has been shown in neurotized and nonneurotized flaps 19–21 with some authors reporting no superior improvement in flaps with nerval reconstruction.…”
mentioning
confidence: 80%
“…The deep inferior epigastric perforator flap (DIEP) is also described to be available for neurotization. The nerve branches of intercostal nerves are described as following the arteriovenous perforators [ 14 ]. Yet, this flap is usually bulkier than the above-described options, and applications for distal extremity reconstruction are, therefore, limited.…”
Section: Neurotizable Workhorse Flapsmentioning
confidence: 99%
“…However, referring to Bijkerk et al 3 would have been appropriate when discussing the length of the procedure. Vartanian et al 1 reported that the overall success in this procedure varies between 65% and 95% and that it increases surgery duration by at least 30 min. An increased surgery duration is to be expected when a double neurorrhaphy is performed and even more so when nerve grafts are required.…”
Section: E T T E R T O T H E E D I T O Rmentioning
confidence: 99%